2006
DOI: 10.1111/j.1600-0579.2006.00388.x
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of staff on student outreach placements

Abstract: These findings provide a planning and evaluation framework for dental educators involved in outreach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
32
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 27 publications
6
32
0
2
Order By: Relevance
“…10,11 Pointers for subsequent development were the importance of individual nursing support and having sufficient students in each location to maintain service volume. Then in 2004 a randomised controlled trial gave firm evidence of the educational benefits of this adjunct to hospital training.…”
Section: Proving and The Decision To Adopt An Expanded Programmementioning
confidence: 99%
“…10,11 Pointers for subsequent development were the importance of individual nursing support and having sufficient students in each location to maintain service volume. Then in 2004 a randomised controlled trial gave firm evidence of the educational benefits of this adjunct to hospital training.…”
Section: Proving and The Decision To Adopt An Expanded Programmementioning
confidence: 99%
“…American experience suggests that in relation to quality, community-based programmes can be at least as effective as school-based experiences in provid ing students with a sound clinical edu cation. 22 Smith et al 20 note that effective communication and adequate resourcing are critical success factors. Other dental schools have adopted different models of outreach.…”
Section: Discussionmentioning
confidence: 99%
“…2,[17][18][19] Consistent with this view, the pilot considered here dem onstrated that in general the students valued the experience and skills they gained from outreach. 9 A British study of staff perspectives on student outreach placements 20 identified positive atti tudes towards outreach, which was seen as providing productive teaching and learning experiences. In the evaluation presented here both the outreach teach ers and dental school academics thought outreach benefited students in a variety of ways.…”
Section: Discussionmentioning
confidence: 99%
“…Each student has a unique profile of experience and skills and therefore there will be some unpredictability in the time and level of supervision any one student will require (Lyon, 2004;Smith et al, 2006). The more clinical staff know about a student before the placement commences, the better they can plan for that placement.…”
Section: Be Prepared For Differences In Student Skills and Experiencementioning
confidence: 99%